What diplomats do the life and work of diplomats - Barder, Brian 1934-
This text describes all aspects of the life of a diplomat through various stages of a typical career. Though following a fictional diplomat, each chapter contains case studies based on the author's thirty years of experience as a diplomat, ambassador, and high commissioner that illustrate key issues